Desain Vaksin Tuberculosis Secara in Silico Untuk Tuberculosis (TBC) Paruparu - Agusinta, Astrid Karindra; Wahjudi, Mariana; Antonius, Yulanda (Syntax Literate, 2025)
Tuberculosis (TB) is one of the 10 high mortality diseases and causes the highest number of deaths caused by Mycobacterium bacteria. The BCG vaccine is a vaccine given in an effort to prevent tuberculosis (TB). The BCG vaccine contains a weakened strain of TB bacteria which aims to build immunity and encourage the body to fight TB if infected. However, someone who received the vaccine as a child is still at risk of being infected with TB. So an alternative vaccine is needed for TB. The proteins used were human TLR and ESAT-6 as positive controls. The ESAT -6 protein is a protein excreted by bacteria which plays a role in virulence when in the human body. This research aims to design potential tuberculosis vaccine design candidates in silico. The method used is selection of target epitope sequences using NCBI, Prediction of transmembrane peptide signals using Signal IP 5.0 and TMHMM, prediction of epitope interactions with T cell and B cell receptors using IEDB, analysis of antigenicity and allegenicity, prediction of epitope interactions with T cell and B cell receptors using the molecular docking method, and analysis using PDBsum. The results show that AGJ67874, OBK19877, GLB86787 show that each has the potential to be an alternative vaccine when compared to ESAT-6 as a standard epitope. The closest result is GLB86787.